Case Report: Pathological diagnosis of left upper lobe nodules: two cases of composite small cell lung cancer and literature review - Zhang, Jishen; Jin, Defeng; Wei, Yutao (Frontiers in Oncology, 2025)
Combined Small Cell Lung Cancer (C-SCLC) is defined by the World Health Organization (WHO) as a combination of Small Cell Lung Cancer (SCLC) and other components, which may include any type of Non-Small Cell Lung Cancer (NSCLC). It is a relatively rare type of lung cancer, with an incidence ranging from 2% to 28%, and its incidence is on the rise. We report two cases of combined small cell lung cancer (C-SCLC) diagnosed by postoperative pathology following thoracoscopic left upper lobectomy at our hospital. One case was small cell carcinoma combined with squamous cell carcinoma (95% SCLC + 5% SCC), while the other was small cell carcinoma combined with large cell carcinoma. Both patients were male with a history of heavy smoking. Postoperatively, they received adjuvant chemotherapy combined with immunotherapy and surgery alone, respectively. No recurrence was observed during follow-up. This paper, in conjunction with a literature review, discusses the clinical and pathological features, diagnosis, potential molecular markers, treatment, and prognosis of C-SCLC. We emphasize the importance of early surgical resection and individualized comprehensive treatment, aiming to provide clinical reference for the diagnosis and management of this rare type of lung cancer.